Vertikalni okvir za poučevanje govornega nastopanja v osnovni šoli za celovito oblikovanje govork in govorcev - Žmavc, Janja (Jezik in slovstvo, 2024)
This paper discusses a proposal for teaching oral performance in primary school. As one of the critical points, we stress the importance of a process-oriented and comprehensive acquisition of oral performance within the primary school, which we highlight through a discussion of some of the common points between the ancient model of rhetorical education and contemporary conceptualizations of oracy. In the second part, we present some of the problem areas in the current curriculum, together with a three-step framework for teaching oral performance. This approach allows for a more successful development of the ability to speak confidently and authentically in public.
Keywords: education; govorno nastopanje; oral presentation; osnovna šola; pouk slovenščine; primary school; retorika; rhetoric; teaching Slovene; vertically based teaching; vertikalno poučevanje; vzgoja in izobraževanje